Analysis and dynamics of the predator-prey: Toxoplasma Gondii and common influenza with associated costs models - Gomez, Rosa (2022)
This work is intended to provide basic information and numerical experimentation of biological models focusing on how computation can be used to generate results via software R. In addition, this work enriches the scientific literature in Spanish that links mathematics and computational biology. It also provides detailed information on the analysis of Predator-prey, Toxoplasma gondii, and Common influency models. For the development of this article we will speak in the first instance of the dynamics of the predator-prey model. In the last two models, it is solved numerically for a range of values of a given parameter. This in order to show deductions that contribute to a deeper investigation of the data involved, and even to the analysis of a professional specialized in the model.